Transient ST Elevation following Anaphylactic Shock: A Case Report of The Potential Kounis Syndrome - Aryadi, I Putu Hendri; Eryana, I Made; Sumajaya, I Dewa Gde Dwi (Jurnal Kardiologi Indonesia, 2025)
Background: Anaphylactic shock rarely can induce allergic-induced acute coronary syndrome known as Kounis Syndrome. It involves the release of inflammatory cytokines through mast cell activation, which leads to coronary artery vasospasm and ST elevations presentation on electrocardiography (ECG).Case Illustration: A 45-years-old woman with unknown past medical history presented with weakness all over the body, dizziness, pain on left hand and history of fainted, immediately after being stung by small wasps. She was in hypotension with wheezing and weak peripheral pulses. Her laboratory examination displayed leukocytosis, thrombocytosis, high level of blood sugar and triglyceride. Initial twelve-lead ECG demonstrated ST-segment elevation on the inferior leads (II, III, and aVF) and reciprocal ST-depression on the lateral lead. Diagnosis of anaphylactic shock caused by insect bite was made, with a potential of becoming Kounis Syndrome. Treatment for anaphylactic shock was initiated with fluid resuscitation, intramuscular epinephrine, intravenous methylprednisolone and ranitidine. Patient’s complaint vanished and the patient discharged in stable condition two days later.Discussion: Kounis Syndrome consists of three main types, including Type I Kounis Syndrome―manifested as coronary artery vasospasm with/without cardiac biomarker elevation among patient without predisposing factor of coronary artery disease. This type differs with the second and third type, which present plaque erosion or thrombosis, leading to myocardial infarction. The treatment for Type 1 Kounis Syndrome mostly in the form of aborting the anaphylactic reaction only, through medication administration until symptoms resolved. Based on this case, the patient was a non-smoker young Asian woman with a low risk (<1% of 10-years-risk) of fatal cardiovascular disease (CVD) in populations with high CVD risk. Clinically, the patient did not show any vascular thrombotic symptoms. In addition, administration of adrenaline, corticosteroid and antihistamine relieved patient's complaint, thus this case can be hypothesized as a potential Type I Kounis Syndrome. Emergency coronary angiography or echocardiography has to be done to clarify the diagnosis of this allergic-induced acute coronary syndrome.Conclusion: Transient ST elevation could happen in some rare cases following an anaphylactic shock. The swift recognition, accurate diagnosis, and prompt treatment are important for optimal outcomes in the probability of Kounis Syndrome.Keywords: anaphylactic shock, Kounis syndrome, ST elevation